2010
DOI: 10.1186/1471-2474-11-245
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral hip replacement reveals superior outcome and fewer complications than two-stage procedures: a prospective study including 1819 patients and 5801 follow-ups from a total joint replacement registry

Abstract: BackgroundTotal joint replacements represent a considerable part of day-to-day orthopaedic routine and a substantial proportion of patients undergoing unilateral total hip arthroplasty require a contralateral treatment after the first operation. This report compares complications and functional outcome of simultaneous versus early and delayed two-stage bilateral THA over a five-year follow-up period.MethodsThe study is a post hoc analysis of prospectively collected data in the framework of the European IDES hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 24 publications
(34 reference statements)
6
70
1
1
Order By: Relevance
“…The likelihood that high-risk patients would undergo contralateral THA was 97%. For these patients, simultaneous bilateral THAs may offer decreased complication rates [1,3,18] and be more costeffective [18]. Parvizi et al [18] reported on 98 patients who received simultaneous bilateral THAs versus 98 patients who received staged bilateral THAs, with a minimum 6-month followup of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood that high-risk patients would undergo contralateral THA was 97%. For these patients, simultaneous bilateral THAs may offer decreased complication rates [1,3,18] and be more costeffective [18]. Parvizi et al [18] reported on 98 patients who received simultaneous bilateral THAs versus 98 patients who received staged bilateral THAs, with a minimum 6-month followup of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers 9 have shown simultaneous bilateral THA to be more effective than staged THA because it allows for substantial improvement in hip motion and better functional recovery. Aghayev et al 10 demonstrated that patients who underwent simultaneous bilateral THA have a lower rate of major systemic complications when compared with two-staged bilateral THA in a study enrolling 1819 patients. Parviziet al 11 demonstrated that there is no difference in systemic complications between unilateral THA and simultaneous bilateral THA.…”
Section: Introductionmentioning
confidence: 99%
“…As has been shown in previous studies, sequential bilateral THA decreases costs [1] and shortens rehabilitation time [11]. Better postoperative outcomes after sequential bilateral THA than after two-stage bilateral THA have been reported in several patient series [22, 23], and have been confirmed in a meta-analysis [12]. With regard to safety, the study findings are in concordance with a recent meta-analysis that concluded that simultaneous bilateral THA does not lead to an unacceptably high rate of complications or rate of death, compared with a staged bilateral approach [12].…”
Section: Discussionmentioning
confidence: 82%